Formulation and Evaluation of Paracetamol Effervescent Tablet - Tambe, Bhavana Dnyandeo (Asian Journal of Pharmaceutical Research and Development, 2021)
Oral dosage forms are the most popular way of taking medication, despite having some disadvantages compared with other methods like risk of slow absorption of the medicament, which can be overcome by administering the drug in liquid form, therefore, possibly allowing the use of a lower dosage. However, instability of many drugs in liquid dosage form limits its use. Effervescent technique can be used as alternate to develop a dosage form which can accelerate drug disintegration and dissolution, is usually applied in quick release preparations. The tablet is added into a glass of water just before administration and the drug solution or dispersion is to be drunk immediately. The tablet is quickly broken apart by internal liberation of CO2 in water due to interaction between tartaric acid and citric acid with alkali metal carbonates or bicarbonates in presence of water. Due to liberation in CO2 gas, the dissolution of API in water as well as taste masking effect is enhanced Along with the development of new pharmaceutical technique, effervescent tablet are more and more extensively to adjust the behavior of drug release, such as in sustained and controlled release preparations, pulsatile drug delivery systems, and so on. In present work an attempt has been made to formulate an effervescent tablet containing immediate release of paracetamol using various acids and bases. In present work we are used different acids and bases in different concentration. The formulation of tablets was done by using wet granulation as well as dry granulation in that technique wet granulation which was found acceptable. Then formulated tablets were evaluated for hardness, friability, weight variation, and disintegration time . From study it was concluded that F5 shows the better result than the F1, F2, and F3 & F4.